Արևմտահայոց «Ազգային սահմանադրության» վերաքննության սկզբունքները - Սարվազյաան, Լիլիթ (Լիմուշ հրատ.)
The article analyzes the procedure and reasons for the revision of the “National Constitution”, the principles of the immutability of fundamental laws, the re-editing of some articles, and the dissolution or addition of new articles. It is argued that the main six principles forming the theoretical-ideological basis of the "National Constitution", and the unwritten principles of constitutional governance reflected in various chapters are not subject to revision Constitutional amendments must be based on: a) the popular will of the people as a natural right, b) the decision of the National Assembly as a legal basis, c) the will of the Porte as the consent of the ruling government. Any constitutional changes made for anti-national purposes are rejected.
Keywords: Փիլիսոփայություն